The ninth month [compact disc, unabridged] - Patterson, James, 1947-; DiLallo, Richard (Hachette Book Group, 2022)
Mother-to-be Emily Atkinson leads a complicated life in New York City. Women in her social circle have gone missing, and she's sure she's being stalked. But without proof, will anyone trust her mother's intuition?